Pengembangan Media Pembelajaran Berbasis Video Tutorial untuk Meningkatkan Efektifitas Pembelajaran pada Mata Kuliah Tata Rias Pengantin Indonesia - Mandalika Mandalika; Syahril Syahril (Universitas Negeri Padang, 2020)
Indonesian Bridal is a practical learning method at Cosmetology education that difficult to understand by student because learning media that used by lecturer not giving the explanation of theory.Based of observation students in Makeup and Beauty Education for Indonesian Bridal that difficult to understand because a learning media not been effected. Based on that problem, the purpose of this research were developing learning mediaof tutorial video that effective on Indonesian Bridal learning. This research used Research and Development (R&D) method, and model that was used is 4D model. There was four steps in 4D model, there were define, design, develop, and disseminate. Edmodo applicationappliedto developing learning media. The result concluded that learning media were effective by effectiveness result was have a significant difference between the control class and experimental class. This learning media can be used as a learning media at Indonesian Bridal.